Evaluation of the in situ polymerization kinetics for the gelcasting of ceramic foams - P. Sepulveda; J.G.P. Binner (2001)
Recent processing technologies have employed the in situ polymerization of organic monomers to consolidate particulate suspensions of ceramics into dense and strong bodies. The same principle has been applied to solidify foamed ceramic suspensions with great success. In this work, the parameters that influence the polymerization kinetics of acrylic monomers were investigated in systems containing the separate components of a ceramic suspension, with and without the generation of foam. The main objective was to obtain control of the onset time for polymerization (I[d]), which is a critical factor in the processing of foamed ceramics. Analysis of the exothermic profiles registered during polymerization revealed that the polymerization onset is markedly influenced by a number of variables, including the solids concentration, initial temperature, pH, and oxygen concentration.